Paralisia de corda vocal e cisto de tiroide - Martins, R. H. [UNESP]; Castilho, E. C.; Ragazzo, R. [UNESP] (My University, 1996)
The authors present a rare case of vocal cord paralysis following thyroid cyst. The clinical diagnostic and evolution aspects are presented. The importance of precise evaluation of the thyroid gland in all cases of vocal cord paralysis is emphasized.
Vocal cord paralysis following thyroid cyst
Keywords: thyroid diseases; vocal cord paralysis; adult; case report; human; male; thyroid cyst